Aspartate β-Hydroxylase (ASPH) Expression in Acute Myeloid Leukemia: A Potential Novel Therapeutic Target - Noa G. Holtzman; Noa G. Holtzman; Michael S. Lebowitz; Rima Koka; Maria R. Baer; Maria R. Baer; Kanam Malhotra; Amir Shahlaee; Hossein A. Ghanbari; Søren M. Bentzen; Søren M. Bentzen; Ashkan Emadi; et al. (Frontiers in Oncology, 2021)
BackgroundAspartate β-hydroxylase (ASPH) is an embryonic transmembrane protein aberrantly upregulated in cancer cells, associated with malignant transformation and, in some reports, with poor clinical prognosis.ObjectiveTo report the expression patterns of ASPH in acute myeloid leukemia (AML).MethodsCell surface expression of ASPH was measured via 8-color multiparameter flow cytometry in 41 AML patient samples (31 bone marrow, 10 blood) using fluorescein isothiocyanate (FITC)-conjugated anti-ASPH antibody, SNS-622. A mean fluorescent intensity (MFI) of 10 was used as a cutoff for ASPH surface expression positivity. Data regarding patient and disease characteristics were collected.ResultsASPH surface expression was found on AML blasts in 16 samples (39%). Higher ASPH expression was seen in myeloblasts of African American patients (p=0.02), but no correlation was found between ASPH expression and other patient or disease characteristics. No association was found between ASPH status and CR rate (p=0.53), EFS (p=0.87), or OS (p=0.17).ConclusionsASPH is expressed on blasts in approximately 40% of AML cases, and may serve as a new therapeutically targetable leukemia-associated antigen.